2022
DOI: 10.3389/fpubh.2021.812735
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Sentiment Analysis Using State-of-the-Art Machine Learning and Deep Learning Techniques

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has influenced the everyday life of people around the globe. In general and during lockdown phases, people worldwide use social media network to state their viewpoints and general feelings concerning the pandemic that has hampered their daily lives. Twitter is one of the most commonly used social media platforms, and it showed a massive increase in tweets related to coronavirus, including positive, negative, and neutral tweets, in a minimal period. The researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Social media health research has shown promising potential and is being utilized for HIV surveillance (Heerden & Young, 2020), observation of opioid usage across the US , and to understand COVID-19 perceptions (Ugarte et al, 2021). The introduction of AI methods to COVID-19 social media research brings forth new ethical concerns and potential harms that require addressing (Ahmed et al, 2021;Jalil et al, 2022). Research principles from the Belmont Report may be utilized to establish best practices for utilizing social media data.…”
Section: Discussionmentioning
confidence: 99%
“…Social media health research has shown promising potential and is being utilized for HIV surveillance (Heerden & Young, 2020), observation of opioid usage across the US , and to understand COVID-19 perceptions (Ugarte et al, 2021). The introduction of AI methods to COVID-19 social media research brings forth new ethical concerns and potential harms that require addressing (Ahmed et al, 2021;Jalil et al, 2022). Research principles from the Belmont Report may be utilized to establish best practices for utilizing social media data.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have also used social media to support the surveillance and monitoring of an epidemic (70)(71)(72). Missier et al (70) identified tweets related to dengue epidemics by classifying them into mosquito, sickness, and news-related classes.…”
Section: Social Media and Internet Searchesmentioning
confidence: 99%
“…These opinions from German-speaking countries were manually labeled, and Beck et al utilized predictions by transformer-based models. Jalil et al ( 71 ) performed sentiment analysis on tweets' text to classify them into positive, negative, and neutral. For the analysis, they used the COVIDSenti dataset ( 78 ) and reached the highest accuracy of 96.66% with the proposed Multi-depth DistilBERT method.…”
Section: Disease Monitoringmentioning
confidence: 99%
“…The Covid-19 (Corona Virus) has been spread around all over the world now, and new cases and death rates are increasing day by day, which is an alarming situation for human life [5][6][7][8]. The Covid-19 pandemic shook the businesses, economy, trading, education [9,10], healthcare, especially the daily lifestyle of everyone globally [11][12][13].…”
Section: Introductionmentioning
confidence: 99%